Evolving global governance structures: Division of labour and co-operation between regional and global security arrangements - Ernst Hildebrandt; Winrich Kühne (Stiftung Wissenschaft und Politik (SWP), 2001)
Zu dieser Studie liegt keine Kurzfassung vor
Keywords: 320